Outcomes of Parenting Interventions for Child Conduct Problems: A Review of Differential Effectiveness - Shelleby, Elizabeth C. (2014)
This review integrates findings from studies formally testing moderators of parenting interventions targeting child conduct problems from ages 1 through 10 with a focus on baseline child problem behavior, sociodemographic risks, and family process risks as moderators. The review examines whether differential effectiveness has been found for individuals at higher versus lower risk across the body of moderator studies of parenting interventions. We conclude that greater problematic child behavior at baseline may, in some cases, be associated with greater benefit from parenting interventions. None of these studies reviewed found reduced effects for those with higher baseline child problem behavior. With regard to sociodemographic and family process risks as moderators, findings are less consistent; however, on the whole, the collection of studies suggests equal effectiveness across levels of risk, with reduced effects for those at higher risk rarely demonstrated. Implications of these conclusions for future research and intervention efforts are discussed.